Transfer of Innovation in Structural Funds - Lower Silesia Case Study - Drelich, Kamila (Transfer innowacji w funduszach strukturalnych na przykładzie Dolnego Śląska, 2010)
The research about EU funds is limited to the basic papers, which is the result of the dynamic nature of application system, differences among regional systems, and between regional and national systems. Non-standard analysis are needed, especially on horizontal and vertical level. The evaluation of final results of II Programming Period 2007-2013 may be oriented at particular variables or holistic perspective. The transfer of innovation by enterprises is important because of increasing the level of competitiveness. The Lower Silesia case study shows that on regional level innovations have a relative dimension, which is a result of purchasing new solutions instead of creating them. the subjects which transfer relative innovations are mainly represented by natural persons conducting business activity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 21-30
Keywords: EU funds; relative innovation phenomenon; Lower Silesia